Acquisition Performance of a BDS Receiver with UWB Impulse Radio Interference - Jin, Yiheng; Lu, Tingting; Zhang, Hao; Gulliver, T. A. (Recent Patents on Engineering, 2018)
Background: Ultra-wideband (UWB) Impulse Radio (IR) systems have been widely applied to some fields according to the recent patents which coexist with Beidou navigation satellite system (BDS), thus UWB signals may act as a broadband interference to BDS receivers and a threat to disrupt their normal operation. Objective: The study aimed to evaluate the acquisition performance of a BDS receiver with UWB-IR interference, and analyze the processing of UWB-IR signals at the radio frequency (RF) front end of the receiver. Methods: A simulation platform including a Beidou-1 (B1) signal source, a noise module, a software RF front end and an acquisition module was constructed. The power spectral density (PSD) of the B1 signal and UWB-IR signals at the RF front end as well as the processing of UWB signals in time domain was analyzed. Acquisition success rates were measured with UWB interference at different modulation modes, different pulse repetition frequencies (PRFs) and different pulse duty cycles. Results: The RF front end provided no significant suppression of UWB-IR interference in both frequency and time domain. It was shown that a lower UWB PRF and a lower pulse duty cycles improve the acquisition performance. In addition UWB-IR signals with different modulation mode had different interference with the acquisition performance. Conclusion: The acquisition performance of a BDS receiver in the presence of interference from an UWB-IR system was examined. The UWB-IR interference still had an effect on the BDS receiver when the UWB power levels were within the permitted range.
Keywords: UWB-IR signal